Inclusive Branding and Visual Communication for Disability-Led MSMEs: Strategies for Social Empowerment and Market Competitiveness - Anisa, Eka (Fast in Humanities, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in fostering economic inclusion, particularly for marginalized communities such as persons with disabilities. However, limited access to effective branding and visual communication strategies often hinders the competitiveness of disability-led or disability-inclusive MSMEs. This study aims to explore how strategic branding and visual communication can enhance the market competitiveness of products developed by disability communities under social empowerment programs. Employing a qualitative case study approach, data were collected through in-depth interviews, field observations, and visual documentation from selected MSMEs supported by social empowerment initiatives. The findings reveal that consistent visual identity, inclusive branding narratives, and audience-oriented packaging design significantly contribute to consumer trust and product differentiation in the market. Moreover, the collaboration between designers and community members proved essential in ensuring that the branding reflects both the values and capabilities of the disability community. This research highlights the transformative role of visual branding in economic empowerment and offers practical insights for inclusive design practices and policy formulation. The study contributes to the interdisciplinary discourse between design, social entrepreneurship, and disability inclusion by emphasizing the strategic integration of visual communication in community-based enterprises.